PELATIHAN DIGITAL MARKETING UNTUK MENINGKATKAN PEMASARAN PRODUK UMKM DESA TANJUNGWADUNG - Nursalim Putra, Hasannudin; Feronita Putri, Indah; Syafa'ah, Nur; Husna Al Fajri, Nidaaul; Arsely, Evalina; Hermono, Budi; Roziqi, Muhammad; Ratna Sari, Linda; Junaidi; Eka Septiviana, Fanesa (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Tanjungwadung Village, located in Kabuh Subdistrict, Jombang Regency, is an area where the majority of the population works as farmers and several residents are involved in Micro, Small, and Medium Enterprises (MSMEs), mostly consisting of small convenience stores and traditional herbal medicine production. However, most MSME actors have not yet utilized digital technology for product marketing. The lack of understanding of digital marketing and limited access to devices and internet networks are the main challenges. Therefore, a community service activity in the form of a Digital Marketing Training was conducted for the local women’s organization (PKK) to enhance their capacity in digital product marketing. This activity was carried out using the Participatory Action Research (PAR) method, which emphasizes active community involvement from the preparation, implementation, to the evaluation stages. The training materials included an introduction to social media as a promotional tool, hands-on practice in creating WhatsApp Business and Instagram accounts, as well as effective marketing communication strategies. The training successfully improved participants' understanding of digital marketing, where initially only four participants used WhatsApp to sell their products. The results of the training showed that participants were enthusiastic throughout each session and were able to apply basic digital marketing techniques. Nevertheless, the program lacked structured and continuous mentoring support. In conclusion, this digital marketing training had a positive impact in fostering digital literacy among MSME actors, yet sustained mentoring is needed to ensure the effective and continuous application of digital marketing practices.